2022
DOI: 10.1149/2162-8777/ac6114
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Thermal Processing on Sn Diffusion and Efficiency Enhancement in Hematite/FTO Photoanodes

Abstract: The frequently underestimated effects of “in air” thermal treatment processing conditions such as temperature, duration, and heating and cooling rates in the design and efficiency of photoelectrodes fabricated for academic studies onto the most common commercial transparent conductive glass substrate i.e. fluorine-doped tin oxide (FTO) were investigated by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, conductive atomic force microscopy, electrochemical impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The furnaces were preheated at employed temperatures and the region where the samples were placed had their temperatures veried by an external thermocouple. Temperatures and duration of thermal treatments adopted in this work were optimized as reported elsewhere 44,45 to preserve the substrate integrity and conductivity. Fig.…”
Section: Synthesis Of Hematite-based Photoanodes By the Polymeric Pre...mentioning
confidence: 99%
“…The furnaces were preheated at employed temperatures and the region where the samples were placed had their temperatures veried by an external thermocouple. Temperatures and duration of thermal treatments adopted in this work were optimized as reported elsewhere 44,45 to preserve the substrate integrity and conductivity. Fig.…”
Section: Synthesis Of Hematite-based Photoanodes By the Polymeric Pre...mentioning
confidence: 99%
“…After the thermal treatment, some interface mismatches are also created [98]. Therefore, the optimization of this process is essential to enhance the hematite PEC performance and to minimize substrate damage [70,[99][100][101][102]. Some studies have been devoted to understanding how the thermal treatment influences the hematite electronic structure, the chemistry of defects in hematite, FTO, and the hematite-FTO interface, as well as the substrate damage caused by the element diffusion from FTO to hematite.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…15−17 Even at higher temperatures, FTO can maintain acceptable conductivities as long as the treatment duration is limited to less than 30 min. 16,17 Undeniably, the substrate selection is impacted by the requirement for thermal treatments in the design of oxidebased photoelectrodes. These treatments can play a strategic role in inducing crystal phase transitions and activating the photoabsorber surface for PEC applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the quest to find a thermal treatment that provides a synergic interaction between the TCO substrate and photoabsorber properties, several studies have been reported. ,,, These studies have highlighted the significance of thermal treatment variables, such as temperature, duration, atmosphere, and even the type of thermal treatment employed in the photoelectrode design. Further insights related to the performance of photoelectrodes composed of TCOs and photoabsorbers such as TiO 2 , CuO, WO 3 , Ta 3 N 5 , and α-Fe 2 O 3 , as well as the influence of thermal treatments and potential interface modifications, can be found elsewhere. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation